2010
DOI: 10.3758/app.72.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Relative priming of temporal local-global levels in auditory hierarchical stimuli

Abstract: Priming is a useful tool for ascertaining the circumstances under which previous experiences influence behavior. Previously, using hierarchical stimuli, we demonstrated (Justus & List, 2005) that selectively attending to one temporal scale of an auditory stimulus improved subsequent attention to a repeated (vs. changed) temporal scale; that is, we demonstrated intertrial auditory temporal level priming. Here, we have extended those results to address whether level priming relied on absolute or relative tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 71 publications
1
7
1
Order By: Relevance
“…Nevertheless, several higher-level mechanisms appear to more likely contribute to the observed differences. First of all, it is important to emphasize that, given the duration of the stimuli in the present study, the local/global interference effects highlighted here should be best understood in the context of relative temporal organizational principles of the auditory system irrespectively of the absolute temporal characteristics or tempi of the melodic sequences (see 29 ). It has to be distinguished from studies concerned with the properties of absolute local-global temporal windows of the auditory system, which can nevertheless exhibit similar types of interactions 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several higher-level mechanisms appear to more likely contribute to the observed differences. First of all, it is important to emphasize that, given the duration of the stimuli in the present study, the local/global interference effects highlighted here should be best understood in the context of relative temporal organizational principles of the auditory system irrespectively of the absolute temporal characteristics or tempi of the melodic sequences (see 29 ). It has to be distinguished from studies concerned with the properties of absolute local-global temporal windows of the auditory system, which can nevertheless exhibit similar types of interactions 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Though most research on attention to hierarchical information has been conducted in the visual modality, various studies have shown that attention to different stimulus scopes also occurs in audition (e.g., Justus and List, 2005;Sanders and Poeppel, 2007;List and Justus, 2010;Ouimet et al, 2012). In auditory studies, as in visual ones, local stimulus patterns are repeated to create an overall global pattern.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Figure 1, the top left hierarchical pattern represents a three-element "falling-rising" pattern repeated three times to create a global "rising-rising" pattern (imagine time elapsing on the x-axis and frequency on the y-axis, as in musical notation). Using such auditory hierarchical stimuli, attentional persistence occurs independently of target pattern, response and absolute scope repetition (Justus and List, 2005;List and Justus, 2010). Because attentional persistence to scope manifests for both vision and audition, one question is whether attentional persistence to a hierarchical level can occur across modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The study explores whether there is any connection between the mechanism of GPE and level-priming that is also closely related to early perceptual processes [ 16 , 17 ] and whether the GPE can be mediated by level-priming. In 1982, Ward conducted an experiment wherein he presented stimuli at the global level or local level.…”
Section: Introductionmentioning
confidence: 99%
“…Level-priming is an automatic attentional persistence to the perceptual scale. This highlights flexibility in the perceptual system; when confronted with repeated-level stimuli, perceivers make use of relative information obtained previously in the early perceptual processes to guide subsequent selection in the global/local tasks [ 16 , 18 ]. Investigating whether this previous information will have some influence on the GPE, which is also closely related to the early perceptual process, is the second purpose of this research.…”
Section: Introductionmentioning
confidence: 99%